Sweet Cherry Byproducts Processed by Green Extraction Techniques as a Source of Bioactive Compounds with Antiaging Properties - Luz Agulló-Chazarra; Isabel Borrás-Linares; Jesús Lozano-Sánchez; Antonio Segura-Carretero; Vicente Micol; María Herranz-López; Enrique Barrajón-Catalán (MDPI AG, 2020)
In the cosmetic industry, there is a continuous demand for new and innovative ingredients for product development. In the context of continual renovation, both cosmetic companies and customers are particularly interested in compounds derived from natural sources due to their multiple benefits. In this study, novel and green-extractive techniques (pressurized solvent, supercritical CO2, and subcritical water extractions) were used to obtain three new extracts from sweet cherry stems, a byproduct generated by the food industry. The extracts were characterized by high-performance liquid chromatography coupled to quadrupole-time-of-flight mass spectrometry (HPLC-ESI-QTOF-MS), and 57 compounds, mainly flavonoids but also organic and phenolic acids, fatty acids, and terpenes, were identified. After analytical characterization, a multistep screening approach, including antioxidant, enzymatic, and photoprotective cellular studies, was used to select the best extract according to its benefits of interest to the cosmetics industry. The extract obtained with supercritical CO2 presented the best characteristics, including a wide antioxidant capacity, especially against lipid peroxyl and •OH free radicals, as well as relevant photoprotective action and antiaging properties, making it a potential new ingredient for consideration in the development of new cosmetics.